An anti-freezing temperature control concrete based on solid waste-based phase change functional aggregate and a preparation method thereof

CN122977792APending Publication Date: 2026-10-27NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611275902.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,现有相变材料在水泥基材料中的应用仍存在一定技术限制

Benefits of technology

本发明提出了一种动态冷缩抗冻机制。不同于传统采用引气剂引入气孔的抗冻方式,本发明利用相变材料在低温条件下液-固相变过程中产生的体积冷缩效应以及在温度变化下的冷缩效应,在多源固废骨架内部形成动态缓冲空间,有效释放孔隙水结冰引起的冻胀应力,从而在保证混凝土抗压强度的基础上,显著提高其抗冻融耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977792A_ABST
    Figure CN122977792A_ABST
Patent Text Reader

Abstract

The application discloses a kind of anti-freezing temperature control concrete based on solid waste-based phase change functional aggregate and a preparation method thereof.The anti-freezing temperature control concrete is composed of the following raw materials in parts by mass: ordinary Portland cement 120-180 parts, stone 94.5-378 parts, sand 141-282 parts, solid waste-based phase change functional aggregate 157.2-628.9 parts, water 40-60 parts, and polycarboxylic acid superplasticizer 3-6 parts.The preparation process of the solid waste-based phase change functional aggregate includes mixing blast furnace slag, desulfurization slag, electrolytic manganese slag, and biochar to obtain dry powder.The mass ratio of the blast furnace slag, desulfurization slag, and electrolytic manganese slag is 6:2-3:1-2.The doping amount of the biochar in the dry powder is 5wt%-15wt%.The concrete has good temperature control capability, frost durability, and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete technology, specifically relating to a freeze-thaw resistant temperature-controlled concrete based on solid waste-based phase change functional aggregates and its preparation method. Background Technology

[0002] The building materials industry has placed higher demands on green and low-carbon development and resource recycling, making the resource utilization of industrial solid waste an important research direction in the field. Large quantities of industrial solid waste, such as desulfurization slag, electrolytic manganese slag, and blast furnace slag, are generated during industrial production processes in metallurgy, chemical industry, and power generation. These industrial solid wastes are typically characterized by large quantities and significant differences in mineral composition and phase structure. Currently, the treatment of industrial solid waste mainly relies on stockpiling, landfilling, or low-value-added comprehensive utilization. This not only occupies a large amount of land resources, but also carries the risk of potential pollution from heavy metal ions, free acid and alkali substances, and soluble salts that may migrate under environmental conditions such as rainwater leaching, posing a potential pollution risk to the surrounding soil and groundwater environment. Furthermore, desulfurization slag, electrolytic manganese slag, and blast furnace slag are rich in mineral components such as silicon, calcium, and aluminum, possessing certain potential cementitious activity and making them important resources for preparing cementitious materials. However, due to significant differences in chemical composition, mineral composition, and reactivity among various industrial solid wastes, existing resource utilization technologies generally suffer from insufficient synergistic utilization efficiency, limited activation effects, inadequate mechanical properties, and weak ability to stabilize and solidify harmful components, making it difficult to achieve high-value and large-scale utilization of multi-source industrial solid wastes. Therefore, how to achieve high-value utilization of the aforementioned multi-source industrial solid wastes has become a crucial technical problem that urgently needs to be solved.

[0003] Meanwhile, as major infrastructure projects develop towards larger scale and more complex service environments, concrete materials not only need to meet basic mechanical performance requirements but also need to possess good temperature control capabilities and long-term durability. Especially in cold-region hydraulic engineering construction, temperature crack control and freeze-thaw resistance improvement of large-volume concrete structures remain key issues affecting project quality and service life. Large-volume concrete releases a large amount of heat of hydration during early hydration. When this internal heat cannot dissipate in time, it easily creates a large temperature difference between the inside and outside of the environment, leading to temperature stress and inducing temperature cracks, affecting the integrity and long-term service performance of the concrete structure. Furthermore, in cold regions or service environments subjected to seasonally low temperatures, the pore water inside the concrete repeatedly freezes and thaws, causing continuous deterioration of the pore structure and leading to problems such as surface erosion, strength reduction, and decreased impermeability, thereby shortening the service life of the concrete structure. To address the issue of temperature cracking in large-volume concrete, existing technologies typically employ measures such as reducing cement usage, adding mineral admixtures, installing cooling water pipes, and optimizing pouring processes to lower the hydration temperature rise and reduce the formation of temperature cracks. For freeze-thaw damage, existing technologies primarily improve the freeze-thaw resistance of concrete by adding air-entraining agents, increasing concrete density, or using antifreeze admixtures. However, these technologies still have certain limitations. For example, installing cooling water pipes increases construction procedures and costs, and requires high-quality control during on-site construction; while air-entraining agents can improve the freeze-thaw resistance of concrete, improper dosage control can introduce excessive air bubbles, leading to a decrease in the concrete's mechanical properties; and relying solely on mineral admixtures or chemical admixtures for performance regulation makes it difficult to simultaneously achieve synergistic improvements in hydration heat regulation, freeze-thaw resistance, and mechanical properties.

[0004] In recent years, phase change materials (PCMs) have been increasingly applied in the preparation of large-volume concrete due to their excellent latent heat storage capacity. Solid-liquid PCMs, in particular, can absorb heat energy during the hydration and release of heat in concrete cement, thereby reducing the peak hydration temperature rise inside the concrete and mitigating temperature stress caused by the temperature difference between the inside and outside. Simultaneously, due to their volume shrinkage characteristics during the liquid-solid phase change and cooling process at low temperatures, they can alleviate the volume expansion caused by the freezing of pore water in low-temperature environments to some extent. However, the application of existing PCMs in cement-based materials still faces certain technical limitations. On the one hand, PCMs are prone to leakage during the liquid state or phase change process, leading to a gradual decline in their temperature control function, which interferes with the cement hydration process and affects the stability of the matrix structure. On the other hand, the interfacial compatibility between PCMs and cement paste is poor; direct incorporation easily leads to interfacial defects, thereby deteriorating the mechanical properties, impermeability, and long-term durability of concrete. Therefore, improving the encapsulation stability, interfacial bonding performance, and long-term service reliability of PCMs in concrete remains a key technical challenge restricting the application of large-volume cedar concrete. Summary of the Invention

[0005] This invention provides a freeze-thaw-resistant temperature-controlled concrete based on phase change functional aggregate. Under the premise of effectively suppressing the leakage of phase change material and preventing strength degradation, it effectively improves the temperature control capability, freeze-thaw resistance and mechanical properties of concrete through the dual synergy of temperature peak reduction and dynamic cold contraction buffer.

[0006] This invention provides a freeze-thaw-resistant and temperature-controlled concrete based on solid waste-based phase change aggregate. The freeze-thaw-resistant and temperature-controlled concrete is composed of the following raw materials in parts by weight: 120-180 parts of ordinary Portland cement, 94.5-378 parts of aggregate, 141-282 parts of sand, 157.2-628.9 parts of solid waste-based phase change functional aggregate, 40-60 parts of water, and 3-6 parts of polycarboxylate superplasticizer. The preparation process of the solid waste-based phase change functional aggregate includes: mixing blast furnace slag, desulfurization slag, electrolytic manganese slag and biochar to obtain dry powder, wherein the mass ratio of blast furnace slag, desulfurization slag and electrolytic manganese slag is 6:2~3:1~2, and the amount of biochar doped in the dry powder is 5wt%~15wt%. The dry powder is mixed and stirred with deionized water to obtain a supersulfate cement slurry. The supersulfate cement slurry is subjected to molding pre-curing, crushing and screening and standard curing in sequence to obtain a porous solid waste skeleton. Molten phase change material is injected into the porous solid waste skeleton in a vacuum environment, and then the surface is coated with slurry to obtain the solid waste-based phase change functional aggregate.

[0007] This invention constructs a high-strength supersulfate framework through the synergistic activation effect of multiple solid waste sources. During the hydration reaction, various solid wastes play a clear synergistic enhancing role: desulfurization slag primarily provides a suitable alkaline environment, promoting the depolymerization of the glass phase structure in the system; electrolytic manganese slag not only acts as a sulfate activator, providing a large number of sulfate ions, but also supplements some active aluminosilicate components; blast furnace slag, as the main material, provides the main source of silicon and aluminum required for the hydration reaction. Under the synergistic effect of alkaline activation by desulfurization slag and sulfate activation by electrolytic manganese slag, the potential activity of blast furnace slag is fully activated, and a large number of needle-like ettringite crystals and amorphous hydrated silicate gels are rapidly generated within the system, thus forming a dense structure. This dense cement matrix not only serves as a high-strength, rigid supporting framework for functional aggregates, effectively preventing a decrease in compressive strength, but the introduction of biochar further optimizes the pore structure of the system, improving the pore structure of the framework, thereby impregnating more phase change materials, and endowing the material with excellent temperature regulation and freeze-thaw resistance when applied to concrete structures.

[0008] The purpose of this invention in controlling the mass ratio of desulfurization slag and electrolytic manganese slag is to achieve the synergistic activation effect of alkaline activators and sulfate activators, so that the dissolution process of blast furnace slag is coordinated with the hydration formation process, thereby improving the hydration process, promoting the formation of hydration products, and reducing the formation of defects and harmful pores inside the skeleton.

[0009] Furthermore, the water-cement ratio in the supersulfate cement paste is 0.35–0.4. The water-cement ratio not only determines the paste's flow properties and pore structure but also directly affects the concentration and migration ability of active ions in the system. When the water-cement ratio is high, the OH- concentration in the pore liquid decreases, weakening the alkali activation effect and hindering the depolymerization of the glassy phase in blast furnace slag and the continuous dissolution of active silica-alumina components, thus reducing the hydration reaction rate. Simultaneously, excess free water forms more capillaries after hardening, reducing the density and mechanical properties of the structure. When the water-cement ratio is low, the paste's flowability decreases, hindering the uniform dispersion and sufficient contact of the reactants, limiting the migration and diffusion of active ions in the system, and thus affecting the continuous activation of blast furnace slag and the subsequent hydration reaction. Therefore, when the water-cement ratio is 0.35–0.4, not only can the blast furnace slag effectively achieve the dissolution of active silica-alumina, but the better flow properties also enable the migration and diffusion of active ions, thereby promoting the hydration reaction.

[0010] Furthermore, the supersulfate cement slurry is injected into a mold and left to cure for 0.5 to 1 day.

[0011] Furthermore, the crushing and screening process uses a natural stone crusher to crush the pre-cured cubic test blocks, and then obtains solid waste-based porous materials with particle sizes of 4.75~20 mm and 2.36~4.75 mm, respectively.

[0012] The particle size range of the solid waste-based porous material corresponds to that of the natural aggregate in concrete, with coarse aggregate ranging from 4.75 to 20 mm and fine aggregate ranging from 2.36 to 4.75 mm. Using a particle size distribution similar to that of natural aggregates avoids significant changes to the original concrete aggregate gradation system due to the incorporation of phase change functional aggregates. This allows the aggregate to directly replace some of the natural coarse and fine aggregates in concrete mixing, while also facilitating the uniform distribution of phase change functional aggregates in the cement paste, ensuring the structural density and mechanical stability of the concrete.

[0013] Furthermore, the standard curing step includes transferring the sieved particles into a standard curing chamber for continued curing until the internal hydration reaction is complete, forming a high-strength porous solid waste skeleton mainly composed of ettringite crystals and hydrated silicate gel.

[0014] Furthermore, the environmental pressure is reduced to -0.08 MPa to -0.05 MPa to create an impregnation environment; then, molten phase change material is injected while maintaining negative pressure, and the impregnation environment temperature must be within the range of 10°C to 20°C higher than the phase change temperature point, until the phase change material submerges the porous solid waste skeleton.

[0015] Furthermore, the supersulfate cement slurry is wrapped around the porous solid waste skeleton impregnated with the phase change material, and solidified to form a dense hardened shell. This effectively inhibits the leakage of the internal phase change material. On the other hand, since the hardened shell has good compatibility with the cement matrix, it can enhance the interfacial bonding ability between the phase change aggregate and the cement-based material, improve the structure of the interfacial transition zone, reduce the penetration of interfacial defects and harmful corrosive media, thereby reducing the risk of deterioration in the interfacial transition zone and improving the freeze-thaw resistance and long-term stability of the concrete.

[0016] Since the core products generated by the homologous slurry hydration provided by this invention are also ettringite crystals and hydrated silicate gels, they not only significantly improve the compatibility of the interface transition zone between functional aggregates and external concrete matrix in terms of chemical properties, but also, with their high-strength dense shell structure, synergistically enhance the overall mechanical load-bearing capacity of phase change functional aggregates.

[0017] Furthermore, the phase change material is selected from at least one of organic phase change materials or inorganic phase change materials; wherein, the organic phase change material includes, but is not limited to, alkanes, fatty acids and their derivatives or polyols, and the inorganic phase change material is an inorganic hydrated salt.

[0018] Furthermore, the phase change material is paraffin wax, and the 28-day compressive strength of the freeze-thaw resistant temperature-controlled concrete is 31.6~42.6 MPa, with the peak hydration temperature rise effectively controlled at 31.8~39.4℃. Meanwhile, after 200 freeze-thaw cycles, its mass loss rate is only 2.5%~4.8%, and the relative dynamic elastic modulus is maintained at 68.4%~85.7%.

[0019] Furthermore, the solid waste-based phase change functional aggregate includes solid waste-based phase change functional fine aggregate and solid waste-based phase change functional coarse aggregate, wherein the solid waste-based phase change functional fine aggregate comprises 78.6 to 419.2 parts and the solid waste-based phase change functional coarse aggregate comprises 52.4 to 314.4 parts.

[0020] Furthermore, the ordinary silicate cement has a strength grade of 42.5 or higher.

[0021] Furthermore, the particle size of the gravel is 4.75~20 mm, and the particle size of the sand is 2.36~4.75 mm.

[0022] On the other hand, the present invention also provides a method for preparing freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregates, comprising: (1) Weighing of raw materials: According to the mix proportion of each component of the antifreeze temperature control concrete, weigh ordinary Portland cement, gravel, sand, phase change functional aggregate, water and polycarboxylate superplasticizer respectively. (2) Dry mixing stage: The weighed dry materials are put into the concrete mixer for dry mixing. The dry mixing time is controlled at 30~60s to ensure that each solid particle can be evenly dispersed. (3) Wet mixing and vibration molding stage: After the water and polycarboxylate superplasticizer are mixed evenly in advance, they are poured into the above dry-mixed mixture and wet-mixed for 90~120s until the rheological properties of the system are stable and a homogeneous concrete mixture is obtained; then, the mixture is put into a special mold pre-coated with release agent and placed on a vibrating table for full vibration to compact and mold, and remove excess air bubbles inside. (4) Standard curing stage: The vibratory-molded concrete specimens are placed at standard room temperature for pre-curing. After the specimens reach the initial setting requirements, they are demolded. After demolding, they are transferred to a standard curing room (temperature 20±2℃, relative humidity not less than 95%) for continuous curing until the specified design age, and finally the finished product of the antifreeze temperature-controlled concrete based on phase change functional aggregate is obtained.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention proposes a dynamic cold contraction antifreeze mechanism. Unlike traditional antifreeze methods that use air-entraining agents to introduce pores, this invention utilizes the volumetric cold contraction effect generated by the liquid-solid phase change of phase change materials under low-temperature conditions and the cold contraction effect under temperature changes to form a dynamic buffer space inside the multi-source solid waste skeleton. This effectively releases the frost heave stress caused by the freezing of pore water, thereby significantly improving the freeze-thaw durability of concrete while ensuring its compressive strength.

[0024] At the same time, this invention also utilizes the excellent latent heat storage performance of phase change materials to absorb some heat during the heat release process of cement hydration, reduce the internal temperature gradient, thereby smoothing the peak adiabatic temperature rise, achieving temperature regulation, and significantly reducing the risk of temperature cracks.

[0025] Furthermore, this invention constructs a high-strength supersulfate cementitious system by synergistically activating blast furnace slag with desulfurization slag and electrolytic manganese slag. Simultaneously, biochar is incorporated to enrich the internal pore structure of the material, providing more loading space for phase change material impregnation, thereby increasing the loading capacity of the phase change material and increasing the volume of the subsequent dynamic buffer space. At the same time, the surface coating process effectively overcomes the technical challenges of easy leakage and poor interfacial compatibility of phase change materials, enhancing the interfacial compatibility between the phase change functional aggregate and the concrete matrix. This invention also achieves high-value utilization of multi-source solid waste, significantly reducing energy consumption and carbon emissions in the production process of artificial aggregates, demonstrating good economic benefits and green environmental protection value. Attached Figure Description

[0026] Figure 1 This is the preparation process of solid waste-based phase change functional aggregates provided in a specific embodiment of the present invention; Figure 2 The present invention provides a preparation process for freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregates in a specific embodiment of the present invention. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. It should be noted that the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the protection scope of the present invention.

[0028] This invention utilizes the mineral composition and potential cementitious activity of industrial solid wastes such as desulfurization slag, electrolytic manganese slag, and blast furnace slag to prepare solid waste-based phase change functional aggregates with phase change material encapsulation functions. These aggregates are then applied to freeze-resistant and temperature-controlled concrete, which is expected to improve the resource utilization level of industrial solid wastes while enhancing the temperature control capability and freeze-resistant durability of large-volume concrete, providing a new technical path for the development of green and low-carbon building materials.

[0029] Example 1 This invention provides a freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate. The freeze-thaw resistant and temperature-controlled concrete is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts aggregate, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based phase change functional coarse aggregate and 78.6 parts are solid waste-based phase change functional fine aggregate.

[0030] The ordinary silicate cement has a strength grade of 42.5 or higher.

[0031] The size of the gravel is 4.75~20 mm, and the size of the sand is 2.36~4.75 mm.

[0032] The preparation process of the solid waste-based phase change functional aggregate is as follows: Figure 1 As shown, specifically: desulfurization slag, electrolytic manganese slag, blast furnace slag and biochar are weighed according to the mass ratio and mixed and stirred; then, molding pre-curing, crushing and screening, and standard curing are carried out in sequence to obtain a porous solid waste skeleton; then, molten phase change material is injected into a vacuum device for vacuum impregnation; finally, the solid waste-based phase change functional aggregate is prepared by surface coating process with slurry.

[0033] The mass ratio of blast furnace slag, desulfurization slag, and electrolytic manganese slag is 6:3:1; the activating material includes electrolytic manganese slag as a sulfate activator and desulfurization slag as an alkaline activator. Furthermore, the biochar content accounts for 10% of the total mass of the aforementioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0034] The mixing process involves placing the uniformly mixed dry powder and deionized water separately in a mixer and mixing them thoroughly to obtain a supersulfate cement paste.

[0035] The molding and pre-curing process involves injecting supersulfate cement slurry into a 40 × 40 × 40 mm slab. 3 It is placed in a cubic mold and then placed indoors for pre-curing for 1 day.

[0036] The crushing and screening process uses a natural stone crusher to crush the pre-cured cubic test blocks, and then obtains solid waste-based porous materials with particle sizes of 4.75~20 mm and 2.36~4.75 mm, respectively.

[0037] The standard curing process involves transferring the sieved particles into a standard curing chamber for further curing until the internal hydration reaction is complete, forming a high-strength porous solid waste skeleton mainly composed of ettringite crystals and hydrated silicate gel.

[0038] The vacuum impregnation process of the phase change material first involves reducing the ambient pressure to -0.06 MPa to create a suitable impregnation environment; then, molten industrial paraffin is injected while maintaining negative pressure, and the impregnation environment temperature is 60°C, until the industrial paraffin completely submerges the aggregate.

[0039] The surface coating process uses desulfurization slag, electrolytic manganese slag, and blast furnace slag as raw materials. After solidification, it can form a dense hardened shell on the surface of the phase change functional aggregate, thereby effectively inhibiting the leakage of internal phase change materials. At the same time, since the core products generated by the hydration of the homologous slurry are also ettringite crystals and hydrated silicate gel, it not only significantly improves the compatibility of the interface transition zone between the functional aggregate and the external concrete matrix in terms of chemical properties, but also, with its high-strength dense shell structure, synergistically enhances the overall mechanical load-bearing capacity of the phase change functional aggregate.

[0040] The method for preparing freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregates described in this embodiment is simple and efficient to operate. Figure 2 As shown, it includes: (1) Weighing of raw materials: According to the predetermined concrete mix proportion, weigh ordinary Portland cement, gravel, sand, phase change functional aggregate, water and polycarboxylate superplasticizer respectively. (2) Dry mixing stage: The weighed dry materials are put into the concrete mixer for dry mixing. The dry mixing time is controlled at 60s to ensure that each solid particle can be evenly dispersed.

[0041] (3) Wet mixing and vibration molding stage: After the water and polycarboxylate superplasticizer are mixed evenly in advance, they are poured into the above dry-mixed mixture and wet-mixed for 120s until the rheological properties of the system are stable and a homogeneous concrete mixture is obtained. Then, the mixture is put into a special mold pre-coated with release agent and placed on a vibrating table for full vibration to compact and mold, and remove excess air bubbles inside.

[0042] (4) Standard curing stage: The vibratory-molded concrete specimens are placed at standard room temperature for pre-curing. After the specimens reach the initial setting requirements, they are demolded. After demolding, they are transferred to a standard curing room (temperature 20±2℃, relative humidity not less than 95%) for continuous curing until the specified design age, and finally the frozen-resistant temperature-controlled concrete based on phase change functional aggregate is obtained.

[0043] Example 2 The difference between this embodiment and Embodiment 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate comprises 52.4 parts, and the solid waste-based phase change functional fine aggregate comprises 104.8 parts.

[0044] Example 3 The difference between this embodiment and Embodiment 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 283.5 parts gravel, 211.5 parts sand, 314.4 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 157.2 parts are solid waste-based phase change functional coarse aggregate, and 157.2 parts are solid waste-based phase change functional fine aggregate.

[0045] Example 4 The difference between this embodiment and Embodiment 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 283.5 parts gravel, 211.5 parts sand, 314.4 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate comprises 104.8 parts, and the solid waste-based phase change functional fine aggregate comprises 209.6 parts.

[0046] Example 5 The difference between this embodiment and Embodiment 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 189 parts gravel, 211.5 parts sand, 471.6 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate and the solid waste-based phase change functional fine aggregate are both 235.8 parts.

[0047] Example 6 The difference between this embodiment and Embodiment 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 189 parts gravel, 211.5 parts sand, 471.6 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate comprises 157.2 parts, and the solid waste-based phase change functional fine aggregate comprises 314.4 parts.

[0048] Example 7 The difference between this embodiment and Embodiment 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 94.5 parts aggregate, 211.5 parts sand, 628.8 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate and the solid waste-based phase change functional fine aggregate are both 314.4 parts.

[0049] Example 8 The difference between this embodiment and Embodiment 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 94.5 parts aggregate, 211.5 parts sand, 628.8 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate is 209.6 parts, and the solid waste-based phase change functional fine aggregate is 419.2 parts.

[0050] Example 9 This embodiment differs from Embodiment 1 in that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:2:2. Furthermore, the biochar content accounts for 10% of the total mass of the aforementioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0051] Example 10 This embodiment differs from Embodiment 1 in that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this embodiment is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate comprises 52.4 parts, and the solid waste-based phase change functional fine aggregate comprises 104.8 parts. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:2:2. Furthermore, the biochar content accounts for 10% of the total mass of the aforementioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0052] Comparative Example 1 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 401.6 parts gravel, 211.5 parts sand, 118 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, there are 59 parts of solid waste-based phase change functional coarse aggregate and 59 parts of solid waste-based phase change functional fine aggregate.

[0053] Comparative Example 2 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 401.6 parts aggregate, 211.5 parts sand, 117.9 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Among them, the solid waste-based phase change functional coarse aggregate is 39.3 parts, and the solid waste-based phase change functional fine aggregate is 78.6 parts.

[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 70.9 parts gravel, 211.5 parts sand, 668.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, the solid waste-based phase change functional coarse aggregate and the solid waste-based phase change functional fine aggregate are both 334.1 parts.

[0055] Comparative Example 4 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 70.9 parts gravel, 211.5 parts sand, 668.1 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Among them, the solid waste-based phase change functional coarse aggregate is 222.7 parts, and the solid waste-based phase change functional fine aggregate is 445.4 parts.

[0056] Comparative Example 5 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 211.5 parts sand, 786 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Among them, the solid waste-based phase change functional coarse aggregate and the solid waste-based phase change functional fine aggregate are 393 parts.

[0057] Comparative Example 6 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 211.5 parts sand, 786.1 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Among them, the solid waste-based phase change functional coarse aggregate is 262 parts, and the solid waste-based phase change functional fine aggregate is 524.1 parts.

[0058] Comparative Example 7 The difference between this comparative example and Example 1 is that the freeze-thaw control concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts of ordinary Portland cement, 472.5 parts of gravel, 211.5 parts of sand, 60 parts of water and 4.5 parts of polycarboxylate superplasticizer.

[0059] Comparative Example 8 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 94.5 parts gravel, 211.5 parts sand, 628.8 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:3:1. Furthermore, the biochar content accounts for 10% of the total mass of the above-mentioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0060] Comparative Example 9 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 94.5 parts gravel, 211.5 parts sand, 628.8 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:0.5:3.5. Furthermore, the biochar content accounts for 10% of the total mass of the aforementioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0061] Comparative Example 10 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 7:1.5:1.5. Furthermore, the biochar content accounts for 10% of the total mass of the above-mentioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0062] Comparative Example 11 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 5:2.5:2.5. Furthermore, the biochar content accounts for 10% of the total mass of the aforementioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0063] Comparative Example 12 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 94.5 parts gravel, 211.5 parts sand, 628.8 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 314.4 parts are solid waste-based coarse aggregate and 314.4 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:1:3. Furthermore, the biochar content accounts for 20% of the total mass of the above-mentioned multi-source solid waste, and the water-cement ratio during mixing is controlled at 0.35.

[0064] Comparative Example 13 The difference between this comparative example and Example 1 is that the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregate in this comparative example is composed of the following raw materials in parts by weight: 150 parts ordinary Portland cement, 378 parts gravel, 211.5 parts sand, 157.2 parts solid waste-based phase change functional aggregate, 60 parts water, and 4.5 parts polycarboxylate superplasticizer. Specifically, 78.6 parts are solid waste-based coarse aggregate and 78.6 parts are solid waste-based fine aggregate. The solid waste-based phase change functional aggregate is prepared from blast furnace slag, electrolytic manganese slag, and desulfurization slag in a mass ratio of 6:1:3. Furthermore, the solid waste-based phase change functional aggregate prepared in this comparative group does not contain biochar, and the water-cement ratio during mixing is controlled at 0.35.

[0065] To scientifically and quantitatively evaluate the comprehensive performance of the freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregates prepared in the above embodiments and comparative examples, this invention conducts tests in accordance with the "Test Procedure for Hydraulic Concrete" (SL / T 352-2020). For the 28-day compressive strength test, concrete with dimensions of 150 × 150 × 150 mm needs to be prepared according to the specification requirements. 3Standard cubic specimens were prepared. After vibration compaction, the specimens were left to stand in the mold for 24 hours, then demolded and transferred to a standard curing chamber for curing for 28 days. The specimens were then placed in the center of the lower platen of a compression testing machine, and a load was continuously and uniformly applied at a loading rate of 18–30 MPa / min until the specimen failed. The ultimate failure load was recorded, and the compressive strength of the specimen was calculated.

[0066] The adiabatic temperature rise test is used to evaluate the heat storage and peak reduction capacity of phase change functional aggregates during the early hydration stage of concrete. During the test, the uniformly mixed concrete mixture is quickly placed in two layers into a dedicated adiabatic test container with a volume of approximately 50 L. Each layer is thoroughly vibrated and compacted before being sealed. The container containing the specimen is then placed in the adiabatic control chamber of the adiabatic temperature rise tester, with a high-precision temperature sensor precisely embedded at the geometric center of the specimen. After closing the chamber door, fully automated data acquisition is initiated. The center temperature is recorded every 0.5 hours for the first 24 hours, every hour from day 1 to 7, and every 3–6 hours from day 7 to 28, with a total test duration of 28 days. The highest temperature peak is extracted from the complete temperature data collected over the entire test period, and the hydration adiabatic temperature rise value of the freeze-thaw resistant temperature-controlled concrete is calculated accordingly.

[0067] The antifreeze performance was evaluated using a rapid freezing method for systematic testing. First, samples with dimensions of 100 × 100 × 400 mm were prepared. 3 Prismatic standard specimens were prepared and cured under standard conditions for 24 days. The specimens were then immersed in water for 4 days and placed in a freeze-thaw testing machine, with the center temperature of the specimens set to alternate regularly between -18±2℃ and 5±2℃ during a single freeze-thaw cycle. After 200 freeze-thaw cycles, the mass loss rate and relative dynamic elastic modulus were measured. The mass loss rate was obtained by calculating the percentage reduction in the specimen's mass before and after the freeze-thaw cycles relative to its initial saturated reference mass, providing a direct representation of the surface spalling and matrix micromaterial loss induced by frost heave stress. Simultaneously, a forced resonance dynamic elastic modulus meter was used to measure the transverse natural frequency of the specimens before and after the freeze-thaw cycle. The relative dynamic elastic modulus was obtained by calculating the ratio of the square of the transverse natural frequency after 200 freeze-thaw cycles to the square of the transverse natural frequency in the initial state. This index can non-destructively and accurately assess the initiation and damage evolution of microcracks inside the matrix, thereby effectively quantifying and verifying the buffering and release mechanism of dynamic shrinkage pores induced by phase change materials on internal frost heave stress.

[0068] Table 1. Performance test results of freeze-thaw controlled concrete based on phase change functional aggregate prepared in the examples and comparative examples. This invention provides a freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change functional aggregates, which effectively solves the technical problem of microcracks and structural damage in large-volume concrete during construction and service due to the accumulation of hydration heat and freeze-thaw environments. Its core mechanism lies in two aspects: firstly, utilizing the excellent latent heat storage characteristics of phase change materials, a large amount of heat is absorbed during the early hydration stage of cement, thereby effectively reducing the peak adiabatic temperature rise and minimizing the internal temperature gradient of the concrete; secondly, utilizing the volumetric shrinkage effect generated by the liquid-solid phase change of the phase change materials under low-temperature conditions, as well as the volumetric shrinkage accompanying cooling, a dynamic buffer space is provided within the dense framework constructed from multi-source solid waste for the expansion of pore water upon freezing, thus effectively releasing frost heave stress. Experimental data show that the dosage of solid waste-based phase change functional aggregates has a significant impact on the mechanical load-bearing capacity, temperature rise control capability, and freeze-thaw durability of the concrete.

[0069] As can be seen from the test data in Table 1, the freeze-thaw resistant and temperature-controlled concretes based on solid waste-based phase change functional aggregates prepared in Examples 1 to 10 of this invention fully meet and exceed the set technical requirements in terms of mechanical properties, temperature control and crack prevention, and freeze-thaw durability. Specifically, the 28-day compressive strength of the specimens in Examples 1 to 10 is all higher than 30 MPa, meeting the engineering mechanics requirements; their hydration temperature rise peak is successfully suppressed between 31.8 and 39.4℃, effectively avoiding the safety hazards caused by temperature cracks induced by excessive internal temperature rise in concrete; after 200 freeze-thaw cycles, the mass loss rate of the specimens in each example is less than 5%, and the relative dynamic elastic modulus is higher than 60%, demonstrating excellent freeze-thaw resistance. This indicates that by introducing the solid waste-based phase change functional aggregates incorporated in this invention into the matrix, concrete can achieve synergistic enhancement of early temperature control and crack prevention and later freeze-thaw durability while maintaining good load-bearing capacity.

[0070] Comparative examples reveal that the dosage of solid waste-based phase change functional aggregates is a core factor in regulating the mechanical strength, temperature control, and freeze-thaw durability of concrete. With increasing solid waste-based phase change functional aggregate dosage, the compressive strength of the concrete decreased from 42.6 MPa to 31.6 MPa. This is due to the porous structure within the functional aggregates and the load from the phase change material, resulting in lower strength compared to aggregates. However, with increased aggregate dosage, the load of phase change material within the concrete specimens significantly increased, leading to a substantial decrease in the peak hydration temperature rise from 39.4℃ to 31.8℃. Simultaneously, after freeze-thaw cycles, the mass loss rate improved from 4.8% to 2.5%, and the relative dynamic modulus of elasticity increased from 68.4% to 85.7%. This demonstrates that, while ensuring the safety of the load-bearing structure, appropriately increasing the dosage of solid waste-based phase change functional aggregates can leverage the volume shrinkage characteristics of phase change materials at low temperatures to create a richer buffer space within the concrete, thereby efficiently absorbing the frost heave stress caused by water freezing and significantly improving freeze-thaw durability.

[0071] Comparative Examples 1 to 13, on the other hand, demonstrate from the opposite perspective that deviations from the scope of this invention in raw material proportions lead to severe performance imbalances in concrete. Firstly, in Comparative Examples 1 and 2, insufficient use of solid waste-based phase change functional aggregate resulted in peak hydration temperature rises of 43.8°C and 43.4°C, respectively, and post-freeze-thaw relative dynamic modulus of elasticity decreased to 58.5% and 57.2%, respectively, failing to meet the set durability standards. Conversely, when excessive aggregate was introduced (as in Comparative Examples 5 and 6), the compressive strength of the concrete decreased to 22.3 MPa and 23.6 MPa, making it highly susceptible to crushing under pressure and load-bearing failure. Secondly, in Comparative Example 7, which did not contain functional aggregate, the peak hydration temperature rise increased to 48.2°C, and the mass loss rate after 200 freeze-thaw cycles reached 6.7%, indicating that without a certain amount of solid waste-based phase change functional aggregate, the concrete would be unable to resist early-age temperature stress and later-age frost heave stress.

[0072] In summary, this invention, by rationally determining the dosage of solid waste-based phase change functional aggregates, achieves synergistic optimization among temperature control and crack prevention, freeze-thaw resistance and durability, and mechanical load-bearing capacity in large-volume concrete at the macroscopic level. This invention overcomes the engineering bottlenecks of complex traditional temperature control processes and the tendency of air-entraining agents to cause strength degradation, realizing the high-value utilization of multi-source industrial solid waste. It provides a green, intelligent, and long-life advanced material solution for high-quality construction of large-volume concrete structures in frigid regions.

[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention. The scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate, characterized in that, The freeze-thaw-resistant temperature-controlled concrete is composed of the following raw materials in parts by weight: 120-180 parts of ordinary Portland cement, 94.5-378 parts of aggregate, 141-282 parts of sand, 157.2-628.9 parts of solid waste-based phase change functional aggregate, 40-60 parts of water, and 3-6 parts of polycarboxylate superplasticizer. The preparation process of the solid waste-based phase change functional aggregate includes: mixing blast furnace slag, desulfurization slag, electrolytic manganese slag and biochar to obtain dry powder, wherein the mass ratio of blast furnace slag, desulfurization slag and electrolytic manganese slag is 6:2~3:1~2, and the amount of biochar doped in the dry powder is 5wt%~15wt%. The dry powder is mixed and stirred with deionized water to obtain a supersulfate cement slurry. The supersulfate cement slurry is subjected to molding pre-curing, crushing and screening and standard curing in sequence to obtain a porous solid waste skeleton. Molten phase change material is injected into the porous solid waste skeleton in a vacuum environment, and then the surface is coated with slurry to obtain the solid waste-based phase change functional aggregate.

2. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The water-cement ratio in supersulfate cement paste is 0.35~0.

4.

3. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The supersulfate cement slurry is injected into a mold and left to cure for 0.5 to 1 day.

4. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The ambient pressure was reduced to -0.08 MPa to -0.05 MPa to create an impregnation environment. Then, molten phase change material was injected while maintaining negative pressure, and the impregnation environment temperature was required to be 10°C to 20°C higher than the phase change temperature point, until the phase change material submerged the porous solid waste skeleton.

5. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The supersulfate cement slurry is wrapped around the surface of the porous solid waste skeleton impregnated with phase change material and solidified to form a dense hardened shell.

6. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The phase change material is selected from at least one of organic phase change materials or inorganic phase change materials; wherein, the organic phase change material includes, but is not limited to, alkanes, fatty acids and their derivatives or polyols, and the inorganic phase change material is an inorganic hydrated salt.

7. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 6, characterized in that, The phase change material is paraffin wax, and the 28-day compressive strength of the freeze-thaw resistant temperature-controlled concrete is 31.6~42.6 MPa, with the peak hydration temperature rise effectively controlled at 31.8~39.4℃. Meanwhile, after 200 freeze-thaw cycles, its mass loss rate is only 2.5%~4.8%, and the relative dynamic elastic modulus is maintained at 68.4%~85.7%.

8. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The solid waste-based phase change functional aggregate includes solid waste-based phase change functional fine aggregate and solid waste-based phase change functional coarse aggregate, wherein the solid waste-based phase change functional fine aggregate comprises 78.6 to 419.2 parts and the solid waste-based phase change functional coarse aggregate comprises 52.4 to 314.4 parts.

9. The freeze-thaw resistant and temperature-controlled concrete based on solid waste-based phase change aggregate according to claim 1, characterized in that, The size of the gravel is 4.75~20 mm, and the size of the sand is 2.36~4.75 mm.

10. A method for preparing freeze-thaw resistant and temperature-controlled concrete based on phase change functional aggregates according to any one of claims 1-9, characterized in that, include: (1) Weighing of raw materials: According to the mix proportion of each component of the antifreeze temperature control concrete, weigh ordinary Portland cement, gravel, sand, phase change functional aggregate, water and polycarboxylate superplasticizer respectively. (2) Dry mixing stage: The weighed dry materials are put into the concrete mixer for dry mixing, and the dry mixing time is controlled at 30~60s; (3) Wet mixing and vibration molding stage: After the water and polycarboxylate superplasticizer are mixed evenly in advance, they are poured into the above dry-mixed mixture and wet-mixed for 90~120s. Then, the mixture is put into a special mold that has been coated with release agent and placed on a vibrating table for full vibration to compact the molding. (4) Standard curing stage: The vibratory-molded concrete specimens are placed at standard room temperature for pre-curing. After the specimens reach the initial setting requirements, they are demolded. After demolding, they are transferred to a standard curing room for continuous curing until the specified design age, and finally the freeze-thaw-resistant temperature-controlled concrete based on phase change functional aggregates is obtained.